IMPROVEMENT OF THE ETHANOL PRODUCTION OF SACCHAROMYCES CEREVISIAE D8 BY THE RANDOM MUTAGENESIS - Le Thuong, Hoang Thi; Thuy, Tran Thi; Hao, Nguyen Quang (Vietnam Journal of Biotechnology, 2018)
Saccharomy cescerevisiae D8 isolated from Queen pineapple extract and selected for high ethanol fermentation activity (12.37% v/v ethanol concentration in fermentation media with a total sugar content of 200 g/L) has been reported previously (Hoang Thi Le Thuong et al., 2017). In this paper, the strain was subjected to random mutagenesis by N-methyl-N-nitro-N-nitrosoguanidine (NTG) and ultraviolet (UV) in order to enhance its ethanol fermentation. The results showed that 1% NTG was more lethal than UV (260 nm, 50 V) to S. cerevisiae D8 at the same time of treatment. The combination of NTG and UV was found to increase the mortality of S. cerevisiae D8. Surviving cells after treatment with NTG and UV combination were identified for ethanol fermentation. Thirteen clones were cabable of fermenting higher ethanol concentration than S. cerevisiae D8 was. Especially, mutant clone NU 120.4 was able to ferment glucose up to the highest ethanol concentration (22% higher than that of S. cerevisiae D8). This mutant clone also showed more tolerant to high ethanol and sugar concentrations in the fermentation medium than that of S. cerevisiae D8. The ethanol fermentation of this mutant was relatively stable in Queen pineapple extract (ethanol concentration of about 15.07 ± 0.12%) and the yield of ethanol fermentation was 92.62 ± 0.2%, while S. cerevisiae D8 gained maximum alcohol concentration of 12.37 ± 0.2%. In the context of the availability of pineapple used as primary source of food processing in Vietnam nowadays, these results showed a potential application of this mutant clone NU 120.4 in brandy production from pineapple extract.